Triazole Resistance Screening in Environmental Aspergillus Species from Pakistan - Moin, Safia; Amanullah, Fatima Syed; Abbas, Manzar; Laiq, Sidra; Farooqi, Joveria; Zafar, Afia; Jabeen, Kauser (Infectious Diseases Journal of Pakistan, 2022)
Background: Globally resistance to azoles is increasingly being recognized and reported in Aspergillus species isolated from environment. Major risk factor for this resistance is the use of azole and related compounds as fungicides in the agriculture. Data from Pakistan in this regard is not available and is needed. Objective: This study aimed to estimate azole resistance in Aspergillus species isolated from soil specimens. Methods: Soil specimens were collected from four cities of Pakistan and was cultured by dissolving in normal saline and further inoculation on azole resistance screening agar. Aspergillus species was identified using conventional method. Screening plates were incubated and interpreted using recommended methodology. Results: Twenty-five soil specimens were screened, and all grew Aspergillus species. Aspergillus niger grew in 24/25 specimens. Azole resistance could not be detected in any of these specimens. Conclusion: Triazole resistance was not detected amongst environmental Aspergillus isolates from Pakistan. This small study provides baseline for further large scale studies in Pakistan.